2017
DOI: 10.1016/j.cmi.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between general practitioners' vaccination recommendations for their patients and practices for their children

Abstract: Objectives: The objectives of our study were to describe the vaccination recommendations by general practitioners (GPs) for their patients and practices for their children, and to identify any discrepancies between them. Methods: Applying multiple correspondence analysis and agglomerative hierarchical cluster analysis to data from a 2014 cross-sectional survey of a national sample of GPs, we constructed a typology based on the patterns of associations between GPs' vaccine recommendations to their patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Furthermore, a great number of healthcare workers (43.6 % of the responders) answered the survey and we observed that healthcare workers were more prone to get vaccinated or to participate in a vaccine clinical trial independently of the perceived risk to get contaminated. However, vaccine hesitancy also affects healthcare workers [15][16][17]. In our study sample, vaccine hesitancy affects 29.3 % of the healthcare workers and 39.9 % of the non-healthcare workers.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, a great number of healthcare workers (43.6 % of the responders) answered the survey and we observed that healthcare workers were more prone to get vaccinated or to participate in a vaccine clinical trial independently of the perceived risk to get contaminated. However, vaccine hesitancy also affects healthcare workers [15][16][17]. In our study sample, vaccine hesitancy affects 29.3 % of the healthcare workers and 39.9 % of the non-healthcare workers.…”
Section: Discussionmentioning
confidence: 70%
“…Vaccine hesitancy is also present among European vaccine providers, both for patients and for themselves [ 26 ]. Part of this comes from fear of vaccine side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The RKI was able to identify the 20 most commonly held reservations of vaccine skeptics and anti-immunization campaigners and on its website provides extensive answers to how to counter these (e9) (eBox). It doesn't seem to be rare even for primary care professionals to be vaccine skeptics (22), and they do not always act in an evidence-based manner (23). Increased personal contributions in those with private health insurance may in future contribute to these patients deciding against vaccinations, for financial reasons (e10).…”
Section: The Clinical Perspectivementioning
confidence: 99%